EDUCATION BUSINESS STRATEGY IN SEGMENTED MARKET (CASE STUDY : ASHFIYA ELEMENTARY SCHOOL) (The Indonesian Journal of Business Administration, 2019)
The development of the world of education at this time is very important considering the distinction between parents and elementary school children, making Ashfiya Elementary School need to make management strategies and marketing, to adapt to the modern world SD Ashfiya always develops value, service quality & sustainable. SD Ashfiya is located on Jalan Riung Arum, Riung Bandung, Bandung City, managed by the Sekar Putri Melati Foundation. Observing several dynamic changes in several parents of Ashfiya Elementary School students for eight years (established in 2010) and threats both internally & externally, this has led the Foundation to analyze the forecast of stakeholders 'demand & threat for the next three years' reach (2022). In writing this thesis described in a qualitative descriptive manner. Some of the hypotheses obtained were reviewed & tested to be used as references in plotting Ashfiya Elementary's marketing plan.Keywords : Parents, Student, School